Ca2+-stimulated adenylyl cyclases as therapeutic targets for psychiatric and neurodevelopmental disorders - Chen, Jiao; Ding, Qi; An, Lulu; Wang, Hongbing (Frontiers in Pharmacology, 2022)
As the main secondary messengers, cyclic AMP (cAMP) and Ca2+ trigger intracellular signal transduction cascade and, in turn, regulate many aspects of cellular function in developing and mature neurons. The group I adenylyl cyclase (ADCY) isoforms, including ADCY1, 3, and 8, are stimulated by Ca2+ and thus functionally positioned to integrate cAMP and Ca2+ signaling. Emerging lines of evidence have suggested the association of Ca2+-stimulated ADCYs with bipolar disorder, schizophrenia, major depressive disorder, post-traumatic stress disorder, and autism. In this review, we discuss the molecular and cellular features as well as the physiological functions of ADCY1, 3, and 8. We further discuss the recent therapeutic development to target the Ca2+-stimulated ADCYs for the potential treatments of psychiatric and neurodevelopmental disorders.